2019
DOI: 10.1177/2058738419828613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short peptides on neuronal differentiation of stem cells

Abstract: It has been demonstrated that short peptides play an important role in the transmission of biological information, modulation of transcription, and restoring genetically conditioned alterations occurring with age. Peptidergic regulation of homeostasis occupies an important place in physiological processes, which lead to the aging of cells, tissues, and organs, consisting in the involution of major regulatory systems-the nervous, the endocrine, and the immune. The effect of AED (Ala-Glu-Asp), KED (Lys-Glu-Asp),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 54 publications
1
40
0
1
Order By: Relevance
“…According to data reported in the literature, the tripeptide H-Glu-Asp-Gly-OH stimulates cell proliferation and protein biosynthesis, and significantly inhibits apoptosis in fibrobasts, increasing resistance of their mitochondria to damaging agents, as revealed in cultured human stomach epitheliocytes [11]. Short peptides were reported to affect the processes of gene expression and H-Glu-Asp-Gly-OH was shown to decrease the synthesis of the proinflammatory enzyme COX-2 along with TNF-α [11,17]. Taking into account that COX-2 is an inducible enzyme, upregulated in inflammation, that leads to overproduction of prostaglandin E2, a well established mediator of pain and inflammation [1,2,5], it may be presumed that COX-2 inhibition with H-Glu-Asp-Gly-OH is one of the explanations for the mild gastroprotective effect of this tripeptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to data reported in the literature, the tripeptide H-Glu-Asp-Gly-OH stimulates cell proliferation and protein biosynthesis, and significantly inhibits apoptosis in fibrobasts, increasing resistance of their mitochondria to damaging agents, as revealed in cultured human stomach epitheliocytes [11]. Short peptides were reported to affect the processes of gene expression and H-Glu-Asp-Gly-OH was shown to decrease the synthesis of the proinflammatory enzyme COX-2 along with TNF-α [11,17]. Taking into account that COX-2 is an inducible enzyme, upregulated in inflammation, that leads to overproduction of prostaglandin E2, a well established mediator of pain and inflammation [1,2,5], it may be presumed that COX-2 inhibition with H-Glu-Asp-Gly-OH is one of the explanations for the mild gastroprotective effect of this tripeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Both our previous studies and data in the literature showed the decrease of expression and activity of NO-synthase, lipid peroxidation processes, level of heat shock protein (HSP) 70 and p65 in experimental gastric lesions in animals under the effect of H-Glu-Asp-Gly-OH [3,11]. Stem cells, capable of differentiation to other cells, and intracellular signal cascades have also been reported to be some of the targets for the effects of the short peptides [11,17].…”
Section: Discussionmentioning
confidence: 99%
“…Interesting and promising aspects of delivery strategy are peptide-based gel matrices to drug encapsulation [ 126 ]. Peptide-based therapeutic drugs induce the neuronal growth, modulate neurogenesis [ 317 ], and finally improve spatial memory. Their diversity prompts personalized therapies [ 40 , 318 ].…”
Section: Peptide-based Therapiesmentioning
confidence: 99%
“…Oligopeptides imitate the extracellular matrix (the most important part of the stem cell niche), which influences the fate of the stem cell [ 336 , 337 ]. Short peptides play an important role in the transmission of bio-information, modulation of transcription, or restoration of genetically conditioned alterations being developed with age [ 317 , 338 ]. In other words, they have geroprotective properties.…”
Section: Peptide-based Therapiesmentioning
confidence: 99%
“…При применении ДНК-микрочиповой технологии был изучен эффект пептидов Lys-Glu, Glu-Trp, Ala-Glu-Asp-Gly, Ala-Glu-Asp-Pro на экспрессию 15247 генов сердца и головного мозга мышей [3]. Пептиды Ala-Glu-Asp-Gly, Lys-Glu, Ala-Glu-Asp, Lys-Glu-Asp индуцируют нейрональную дифференцировку стволовых клеток тканей зуба человека (hPDLSCs) и являются перспективными для изучения в качестве модуляторов нейрогенеза [4]. Пептиды специфически регулируют экспрессию определенной группы генов и синтез соответствующих белков.…”
unclassified